The first adolescent case of Fraser syndrome 3, with a novel nonsense variant in GRIP1 - Koprulu, Mine; Kumare, Aneeta; Bibi, Anisa; Malik, Sajid; Tolun, Aslıhan (Wiley, 2021)
AbstractFraser syndrome is characterized by cryptophthalmos, syndactyly and other autopod defects, and abnormalities of the respiratory and urogenital tracts. Biallelic variants in GRIP1 can cause Fraser syndrome 3 (FRASRS3), and five unrelated FRASRS3 cases have been reported to date. Four cases are fetuses with homozygous truncating variants. The remaining case is an almost 9‐year‐old Turkish girl compound heterozygous for a truncation variant and a possibly frame‐shift intragenic deletion. We present a 15.5‐year old Pakistani boy with homozygous truncating variant c.1774C>T (p.Gln592Ter). Of the hallmarks of the disease, the boy has cryptophthalmia, midface retrusion, very low anterior hairline, hair growth on temples extending to the supraorbital line and also on alae nasi, agenesis of right kidney, and cutaneous syndactyly of fingers and toes but no symptoms in any other organs, including lungs, anorectal system, genitalia, and umbilical system. This case is the oldest known individual with FRASRS3, and our findings show that a homozygous GRIP1 truncating variant can manifest with a non‐lethal phenotype than in the reported cases with such variants, expanding the phenotypic and mutational spectrum of GRIP1.
Keywords: Male; Adolescent; Eyelids; Nerve Tissue Proteins; Fetus; Mutation; Humans; Abnormalities, Multiple; Female; Genetic Predisposition to Disease; Syndactyly; Carrier Proteins; Child; Fraser Syndrome